[Rezension von: Pinto, Sarah: Where there is no midwife] - Bärnreuther, Sandra (Anthropos, 2011)
eBook: Pinto, Sarah: Where There Is No Midwife. Birth and Loss in Rural India (ISSN0257-9774) von aus dem Jahr 2011